Challenges and Strategic Issues in Regional Development: Analysis of Regional Performance Enhancement Strategies - Husnah, Husnah; Adam, Rosida P. (LifeSciFi, 2022)
This research focuses on examining the challenges and strategic issues in the regional development of Palu, Central Sulawesi. Using a qualitative approach, the study identifies crucial issues and aspirations of the city's residents for the future. The research highlights five strategic issues, including environmental concerns, disaster management, economic growth, public safety, and governance, which have been identified as critical obstacles in achieving sustainable development in Palu. Through a comprehensive analysis of various sources, including literature studies, focus group discussions, public workshops, and surveys, the study develops a roadmap for Palu's development plan from 2021 to 2026. The identified strategic issues serve as key areas for targeted solutions to facilitate a more inclusive and sustainable future for the city. The research provides theoretical insights into urban planning and sustainable development practices and has practical implications for policymakers, aiding them in formulating effective policies. The recommendations offer a framework for regional performance enhancement, contributing to the achievement of the Sustainable Development Goals and the overall well-being of Palu's residents. By encouraging collaborative efforts between the government, civil society, and stakeholders, this study aims to create a better future for Palu and its citizens through strategic regional development.